Estudo do comportamento à abrasão e formação de revestimentos aplicados por GTAW com dupla alimentação de arames tubulares - Colaco, Fernando Henrique Gruber (2021)
The present work investigates the formation of coatings using double feeding of tubular wires and the role of the microstructure against the mechanisms of abrasive wear. This study presents an original method, Flux-Cored-Double-Wire GTAW (FCDW-GTAW), where wires of different compositions were used simultaneously to obtain different microstructures. The study was divided by the steps of manufacturing the bead and the performance of the obtained microstructures. For this, a matrix of Central Composite Design (CCD) of five factors and five levels was used to conduct experiments with GTAW: welding current, welding speed, standoff distance, torch angle, and feed pulse frequency wire. As a result of the manufacturing step, models to determine the geometry and dilution were obtained. The importance of the welding current and speed have on the effects on the weld bead. Six coatings were deposited on AISI1020 steel substrate in the performance step by combining the Fe-Cr-C, Fe-Cr-Cnb, Fe-Cr-C-Mo-Nb and Fe-Cr-C-Mo-Ti tubular wires. The result of the combination of these wires was a hypoeutectic microstructure with niobium and titanium carbides, with an average hardness of 650 HV0,3 and hypereutectic microstructures formed by different levels of niobium, with a microhardness variation from 820 to 1020 HV0,3. These microstructures’ performance was verified in abrasion tests on a macroscopic scale (linear scratching) and microscopic scale (microabrasion). In the scratch tests, a progressive load between 20 and 180 N was used in an HRC geometry penetrator to check the wear mechanisms and width. The coefficient of friction and cross-sectional images confirmed that the hypoeutectic microstructure showed more significant deformation than the hypereutectic ones. The average free path of carbide did not increase the abrasion resistance on a macroscopic scale. However, the hardness of the coating was decisive to minimize the wear width caused by the penetrator. In order to carry out the microabrasion tests, SiO2 and Al2O3 abrasives were used in the fraction of 2% diluted with distilled water, using conditions to reproduce the scratching mechanism with the “free sphere” test method and the normal load of 0.8 N. The wear results confirm the scratching mechanism in all samples tested with alumina and silica, except for the hypoeutectic microstructure worn with silica. The wear coefficient resulting from the alumina tests was higher than the results obtained with the abrasive silica. Wear resistance was determined mainly by the mean free path and by the fraction of MC type carbides and not by the matrix hardness. In conclusion, the resistance to linear scratching for microstructures composed of hard second phase depends on the degree of deformation imposed by the abrasive agent. In the case of tests on a microscopic scale, wear resistance was mainly affected by the coating’s hardness and started to depend on the hardness and fraction of the second hard phase when adequately supported by the matrix.